LINGUISTIC ERRORS ON NARRATIVE TEXT TRANSLATION USING GOOGLE TRANSLATE - Anggaira, Aria Septi (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2017)
This study aims to identify and analyze errors of language aspects that appear on the machine translator from Google-Translate on narrative texts in English into Indonesian. Based on the results of the analysis, it is showed that the morphological aspects occupy the highest positions in the data summary types of errors, as many as 13 errors. Next is the syntactic aspect for 9 errors, and morphology of for 12 errors. It can be concluded that the translation using Google Translate is not the right solution for someone who wants to translate foreign language text, especially if it is used in the learning process at schools.